Pengaruh Nilai Pelanggan (Customer Value) Terhadap Keputusan Pembelian Mixue Ice Cream & Tea (Survei Pada Pelanggan Mixue Ice Cream & Tea) - Amelia, Corrinna Salsabila; Yuliarti, Almira Dwi; Yusuf, Abdul (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to learn about the effect of customer value on purchasing decisions for mixue ice cream & tea. The data type in this study is quantitative, with the population being consumers or customers who have made purchase transactions for mixed ice cream & tea with a sample size of 100 respondents. The data analysis techniques include validity and reliability tests, classical assumptions, and simple regression analysis. In this case, customer value is the independent variable, and purchasing decisions are the dependent variable. The results of this study indicate that customer value affects buying decisions. The results of this study suggest that customer value has a positive effect on buying decisions